Identification of microRNAs and Their Target Genes Explores miRNA-Mediated Regulatory Network of Cytoplasmic Male Sterility Occurrence during Anther Development in Radish (Raphanus sativus L.) - Zhang, Wei; Xie, Yang; Xu, Liang; Wang, Yan; Zhu, Xianwen; Wang, Ronghua; Zhang, Yang; Muleke, Everlyne M.; Liu, Liwang (Frontiers in Plant Science, 2016)
MicroRNAs (miRNAs) are a type of endogenous non-coding small RNAs that play critical roles in plant growth and developmental processes. Cytoplasmic male sterility (CMS) is typically a maternally inherited trait and widely used in plant heterosis utilization. However, the miRNA-mediated regulatory network of CMS occurrence during anther development remains largely unknown in radish. In this study, a comparative small RNAome sequencing was conducted in floral buds of CMS line ‘WA’ and its maintainer line ‘WB’ by high-throughput sequencing. A total of 162 known miRNAs belonging to 25 conserved and 24 non-conserved miRNA families were isolated and 27 potential novel miRNA families were identified for the first time in floral buds of radish. Of these miRNAs, 28 known and 14 potential novel miRNAs were differentially expressed during anther development. Several target genes for CMS occurrence-related miRNAs encoding important transcription factors and functional proteins, which might be involved in multiple biological processes including auxin signaling pathways, signal transduction, miRNA target silencing, floral organ development and organellar gene expression. Moreover, the expression patterns of several CMS occurrence-related miRNAs and their targets during three stages of anther development were validated by qRT-PCR. In addition, a potential miRNA-mediated regulatory network of CMS occurrence during anther development was firstly proposed in radish. These findings contribute new insights into complex miRNA-mediated genetic regulatory network of CMS occurrence and advance our understanding of the roles of miRNAs during CMS occurrence and microspore formation in radish and other crops.